Arene diazonium saccharin intermediates: a greener and cost-effective alternative method for the preparation of aryl iodide - Zaharani, Lia; Khaligh, Nader Ghaffari; Shahnavaz, Zohreh; Johan, Mohd Rafie (TUBITAK, 2020)
In the current protocol, the arene diazonium saccharin derivatives were initially produced from various substituted aromatic amines; subsequently, these intermediates were treated with a greener organic iodide for the preparation of the aryl iodide. We tried to choose low-cost, commercially available, biodegradable, recoverable, ecofriendly, and safe reagents and solvents. The arene diazonium saccharin intermediates could be stored in the liquid phase into a refrigerator for a long time with no significant loss activity. The outstanding merits of the current protocol (a) included the partial recovering of saccharin and tetraethylammonium salt, (b) reduce the use of solvents and the reaction steps due to eliminating separation and purification of intermediates, (c) good yield of the sterically hindered substrates, and (d) avoid the generation of heavy metal or corrosive waste. © TÜBİTAK